2018
DOI: 10.32404/rean.v5i1.1759
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Soybean Genotypes to White Mold in Distinct Agroecosystems

Abstract: White mold (Sclerotinia sclerotiorum) is one of the most important fungal diseases that affect soybean, primarily due to the production of resistant structures called sclerotia. The disease is difficult to control, and sources of genetic resistance are poorly understood. As such, the present study aimed to assess the resistance of soybean genotypes to white mold in two agroecosystems in the Brazil (Barreiras-BA, and Jataí-GO) and analyze the relationship between the disease incidence and the phenotypic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
(24 reference statements)
0
2
0
2
Order By: Relevance
“…Several studies have shown that partial resistance to WM in soybean has been identified, but current resistance sources of commercial cultivars are limited and do not prevent significant crop yield loss (Andrade et al, 2018;Kim and Diers, 2000). Based on the grain yield (GY), 11 transgressive genotypes stood out in this population for their higher grain yield (GY = 31.74 to 52.50 grams) (Table 4).…”
Section: Cycle and Production From The Moderately Resistant Genotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that partial resistance to WM in soybean has been identified, but current resistance sources of commercial cultivars are limited and do not prevent significant crop yield loss (Andrade et al, 2018;Kim and Diers, 2000). Based on the grain yield (GY), 11 transgressive genotypes stood out in this population for their higher grain yield (GY = 31.74 to 52.50 grams) (Table 4).…”
Section: Cycle and Production From The Moderately Resistant Genotypesmentioning
confidence: 99%
“…The averages of PHM in P2 (115.00 cm), F 1 (123.25 cm) and F 2 (123.37 cm) generations were close to the recommended values (Table 5). According to Andrade et al (2018), another important point to consider is whether plants are at an ideal height, without the occurrence of lodging, thereby allowing good air circulation and quicker drying within the crop canopy. It is worth noting that these factors can significantly reduce the intensity of WM (Andrade et al, 2018).…”
Section: Agronomic Trait Statistics In the Segregating Populationmentioning
confidence: 99%
“…Somente em 1882 no Brasil, a partir do relato de Gustavo D'utra incentivou o cultivo desta oleaginosa em território brasileiro, no entanto, as cultivares não tiveram boa adaptação ao Sul do Estado da Bahia onde foi foram plantas as primeiras sementes de soja. Em 1908 cultivares especificas para o consumo humano trazidas por imigrantes japoneses, foram introduzidas oficialmente no Brasil, em meados de 1924 iniciou-se os primeiros cultivos comerciais, tornando a soja umas das principais culturas de importância econômica para o país (Gazzoni, 2018;Andrade et al, 2018;Fachinelli et al, 2021).…”
Section: Introductionunclassified
“…Na safra 2019/20, a área cultivada foi de 36,8 milhões de hectares, produzindo um total de 120,4 milhões de toneladas, estando a frente dos EUA que na safra 2020 produziram 96,84 milhões de toneladas, seguidos pela Argentina que atingiu a marca de 50 milhões de toneladas de soja. A maior área plantada no Brasil, se concentra no Estado de Mato Groso, com 9,98 milhões de hectares atingindo a produção de 35,9 milhões de toneladas, estando em segundo lugar o Estado do Rio Grande do Sul com 6,0 milhões de hectares com produção de 20,1 milhões de toneladas, e em terceiro o Estado do Paraná com 5,6 milhões de hectares, atingindo a marca de 19,8 milhões de toneladas, que vem sendo afetado ano após ano por estiagens, impactando de forma significativa as médias de produtividade (Freitas, 2011;Andrade et al, 2018;Conab, 2020).…”
Section: Introductionunclassified